Future climate projections in the global coastal ocean - Jason Holt; Anna Katavouta; Joanne Hopkins; Laurent O. Amoudry; Christian M. Appendini; Lars Arneborg; Alex Arnold; Yuri Artioli; Jerome Aucan; Barbara Berx; Laura Cagigal; Michela De Dominicis; et al. (Progress in Oceanography, 2025)

Correction: Seasonal forecasting of the European North-West shelf seas: limits of winter and summer sea surface temperature predictability - Jamie R. C. Atkins; Jonathan Tinker; Jennifer A. Graham; Adam A. Scaife; Paul R. Halloran (Climate Dynamics, 2025)

Seasonal forecasting of the European North-West shelf seas: limits of winter and summer sea surface temperature predictability - Jamie R. C. Atkins; Jonathan Tinker; Jennifer A. Graham; Adam A. Scaife; Paul R. Halloran (Climate Dynamics, 2024)
The European North-West shelf seas (NWS) support economic interests and provide environmental services to adjacent countries. Expansion of offshore activities, such as renewable energy infrastructure, aquaculture, and growth of international shipping, will place increasingly complex demands on the marine environment over the coming decades. Skilful forecasting of NWS properties on seasonal timescales will help to effectively manage these activities. Here we quantify the skill of an operational large-ensemble ocean-atmosphere coupled global forecasting system (GloSea), as well as benchmark persistence forecasts, for predictions of NWS sea surface temperature (SST) at 2–4 months lead time in winter and summer. We identify sources of and limits to SST predictability, considering what additional skill may be available in the future. We find that GloSea NWS SST skill is generally high in winter and low in summer. GloSea outperforms simple persistence forecasts by adding information about atmospheric variability, but only to a modest extent as persistence of anomalies in the initial conditions contributes substantially to predictability. Where persistence is low – for example in seasonally stratified regions – GloSea forecasts show lower skill. GloSea skill can be degraded by model deficiencies in the relatively coarse global ocean component, which lacks dynamic tides and subsequently fails to robustly represent local circulation and mixing. However, “atmospheric mode matched” tests show potential for improving prediction skill of currently low performing regions if atmospheric circulation forecasts can be improved. This underlines the importance of coupled atmosphere-ocean model development for NWS seasonal forecasting applications.

Twenty-first century marine climate projections for the NW European shelf seas based on a perturbed parameter ensemble - Jonathan Tinker; Matthew D. Palmer; Benjamin J. Harrison; Enda O'Dea; David M. H. Sexton; Kuniko Yamazaki; John W. Rostron (Ocean Science, 2024)
The northwest European shelf (NWS) seas are environmentally and economically important, and an understanding of how their climate may change helps with their management. However, as the NWS seas are poorly represented in global climate models, a common approach is to dynamically downscale with an appropriate shelf sea model. We develop a set of physical marine climate projections for the NWS. We dynamically downscale 12 members of the HadGEM3-GC3.05 perturbed parameter ensemble (approximately 70 km horizontal resolution over Europe), developed for UKCP18, using the shelf sea model NEMO CO9 (7 km horizontal resolution). These are run under the RCP8.5 high-greenhouse-gas-emission scenario as continuous simulations over the period 1990–2098. We evaluate the simulations against observations in terms of tides, sea surface temperature (SST), surface and near-bed temperature and salinity, and sea surface height. These simulations represent the state of the art for NWS marine projections. We project an SST rise of 3.11 °C (± 2σ = 0.98 °C) and a sea surface salinity (SSS) freshening of −1.01 (± 2σ = 0.93; on the (unitless) practical salinity scale) for 2079–2098 relative to 2000–2019, averaged over the NWS (approximately bounded by the 200 m isobar and excluding the Norwegian Trench, the Skagerrak and Kattegat), a substantial seasonal stratification increase (23 d over the NWS seas), and a general weakening of the NWS residual circulation. While the patterns of NWS changes are similar to our previous projections, there is a greater warming and freshening that could reflect the change from the A1B emissions scenario to the RCP8.5 concentrations pathway or the higher climate sensitivity exhibited by HadGEM3-GC3.05. Off the shelf, south of Iceland, there is limited warming, consistent with a reduction in the Atlantic Meridional Overturning Circulation and associated northward heat transport. These projections have been publicly released, along with a consistent 200-year present-day control simulation, to provide an evidence base for climate change assessments and to facilitate climate impact studies. For example, we illustrate how the two products can be used to estimate climate trends, unforced variability and the time of emergence (ToE) of the climate signals. We calculate the average NWS SST ToE to be 2034 (with an 8-year range) and 2046 (with a 33-year range) for SSS. We also discuss how these projections can be used to describe NWS conditions under 2 and 4 °C global mean warming (compared with 1850–1900), as a policy-relevant exemplar use case.

Climate change projections of commercial fish distribution and suitable habitat around north western Europe - Bryony L. Townhill; Elena Couce; Jonathan Tinker; Susan Kay; John K. Pinnegar (Fish and Fisheries, 2023)
Under future climate change, modification of temperature and salinity are expected to result in distribution shifts of marine organisms, including commercial fish and shellfish. Changes are anticipated everywhere, including in the seas of many important fishing nations. Species turnover will in turn result in both opportunities and threats to fishing industries. To determine the impacts for northwest European shelf fisheries, we project changes for 49 commercially important fish and shellfish species using an ensemble of five ecological niche models and three different downscaled climate change projections. The habitat suitability and latitudinal shifts projected from the recent past (1997–2016) to two futures (2030–2050; 2050–2070) were calculated for waters around the United Kingdom. Of the species examined, around half were projected to have consistently more suitable habitat in the future, including European seabass ( Dicentrarchus labrax , Moronidae), sardine ( Sardina pilchardus , Alosidae) and anchovy ( Engraulis encrasicolus , Engraulidae). Conversely, it is suggested that UK waters will become less suitable for species including Atlantic cod ( Gadus morhua , Gadidae) and saithe ( Pollachius virens , Gadidae). Our comprehensive approach using a number of models and climate change scenarios shows that while there are differences in the magnitude of change between models, and while some models perform better for certain species compared with others, overall, the general trends in habitat suitability and abundance are robust across models and climate scenarios. This emphasises the value in using more than one modelling technique with different climate scenarios (i.e., an ensemble approach) to capture the uncertainty or agreement around climate change projections.

The influence of tides on the North West European shelf winter residual circulation - Jonathan Tinker; Jeff A. Polton; Peter E. Robins; Matthew J. Lewis; Clare K. O’Neill (Frontiers in Marine Science, 2022)
Tides contribute to the large-scale residual circulation and mixing of shelf seas. However, tides are typically excluded from global circulation models (GCMs) so their modelled residual circulation (and mixing) in shelf seas may be systematically wrong. We focus on circulation as it is relatively unexplored, and affects shelf temperature and salinity, potentially biasing climate impact studies. Using a validated model of the North West European Shelf Seas (NWS), we show the essential role of tides in driving the residual circulation, and how this affects the NWS temperature and salinity distribution. Over most of the NWS, removing the tides increases the magnitude of residual circulation while in some regions (such as the Irish Sea) it leads to a reduction. Furthermore, we show that modelling the NWS without tides leads to a cold fresh bias in the Celtic Sea and English Channel (of >0.5°C, and >0.5 psu). This shows that NWS tidal dynamics are essential in the transport of heat and matter, and so must be included in GCMs. We explore two processes by which the tides impact the residual circulation and investigate whether these could be parameterised within non-tidal GCMs: (1) Enhancing the seabed friction to mimic the equivalent energy loss from an oscillating tidal flow; (2) Tidal Phase-driven Transport (TPT), whereby tidal asymmetry drives a net transport due to the phase between tidal-elevation and velocities (equivalent to the bolus term in oceanographic literature). To parameterise TPT, we calculate a climatology of this transport from a harmonic analysis from the tidal model and add it as an additional force in the Navier Stokes equations in the non-tidal model. We also modify the bed drag coefficient to balance the bed stress between the simulations – hypothesising that using this modified drag coefficient will simulate the effect of the tides. This tends to improve the mean and variability of the residual circulation, while the TPT improves the spatial distribution and temporal variability of the temperature and salinity. We show that our proof-of-concept parameterisation can replicate the tidally-driven impact on the residual circulation without direct simulation, thus reducing computational effort.

Towards Winter Seasonal Predictability of the North West European Shelf Seas - Jonathan Tinker; Leon Hermanson (Frontiers in Marine Science, 2021)
We investigate the winter predictability of the North West European shelf seas (NWS), using the Met Office seasonal forecasting system GloSea5 and the Copernicus NWS reanalysis. We assess GloSea5’s representation of NWS climatological winter and its skill at forecasting winter conditions on the NWS. We quantify NWS winter persistence and compare this to the forecast skill. GloSea5 simulates the winter climatology adequately. We find important errors in the residual circulation (particularly in the Irish Sea) that introduce temperature and salinity biases in the Irish Sea, English Channel, and southern North Sea. The GloSea5 winter skill is significant for SST across most of the NWS but is lower in the southern North Sea. Salinity skill is not significant in the regions affected by the circulation errors. There is considerable NWS winter temperature and salinity persistence. GloSea5 exhibits significant predictive skill above this over ∼20% of the NWS, but for most of the NWS this is not the case. Dynamical downscaling is one method to improve the GloSea5 simulation of the NWS and its circulation, which may reduce biases and increase predictive skill. We investigate this approach with a pair of case studies, comparing the winters of 2010/2011 and 2011/2012 (with contrasting temperature and salinity anomalies, and NAO state). While 2 years are insufficient to assess skill, the differences in the simulations are evaluated, and their implications for the NWS winter predictability are considered. The NWS circulation is improved (where it was poor in the GloSea5), allowing more realistic advective pathways for salinity (and temperature) and enhancing their climatological spatial distributions. However, as the GloSea5 SST anomaly is already well simulated, downscaling does not substantially improve this – in other seasons or for other variables, downscaling may add more value. We show that persistence of early winter values provides some predictive skill for the NWS winter SST, and that the GloSea5 system adds modestly to this skill in certain regions. Such information will allow prospective end-users to consider how seasonal forecasts might be useful for their sector, providing the foundation on which marine environmental seasonal forecasts service and community may be developed for the NWS.

Dynamical downscaling of unforced interannual sea-level variability in the North-West European shelf seas - Jonathan Tinker; Matthew D. Palmer; Dan Copsey; Tom Howard; Jason A. Lowe; Tim H. J. Hermans (Climate Dynamics, 2020)
Variability of Sea-Surface Height (SSH) from ocean dynamic processes is an important component of sea-level change. In this study we dynamically downscale a present-day control simulation of a climate model to replicate sea-level variability in the Northwest European shelf seas. The simulation can reproduce many characteristics of sea-level variability exhibited in tide gauge and satellite altimeter observations. We examine the roles of lateral ocean boundary conditions and surface atmospheric forcings in determining the sea-level variability in the model interior using sensitivity experiments. Variability in the oceanic boundary conditions leads to uniform sea-level variations across the shelf. Atmospheric variability leads to spatial SSH variability with a greater mean amplitude. We separate the SSH variability into a uniform loading term (change in shelf volume with no change in distribution), and a spatial redistribution term (with no volume change). The shelf loading variance accounted for 80% of the shelf mean total variance, but this drops to ~ 60% around Scotland and in the southeast North Sea. We analyse our modelled variability to provide a useful context to coastal planners and managers. Our 200-year simulation allows the distribution of the unforced trends (over 4–21 year) of sea-level changes to be quantified. We found that the 95th percentile change over a 4-year period can lead to coastal sea-level changes of ~ 58 mm, which must be considered when using smooth sea level projections. We also found that simulated coastal SSH variations have long correlation length-scales, suggesting that observations of interannual sea-level variability from tide gauges are typically representative of > 200 km of the adjacent coast. This helps guide the use of tide gauge variability estimates.

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

Improving sea-level projections on the Northwestern European shelf using dynamical downscaling - Tim H. J. Hermans; Jonathan Tinker; Matthew D. Palmer; Caroline A. Katsman; Bert L. A. Vermeersen; Aimée B. A. Slangen (Climate Dynamics, 2020)
Changes in ocean properties and circulation lead to a spatially non-uniform pattern of ocean dynamic sea-level change (DSLC). The projections of ocean dynamic sea level presented in the IPCC AR5 were constructed with global climate models (GCMs) from the Coupled Model Intercomparison Project 5 (CMIP5). Since CMIP5 GCMs have a relatively coarse resolution and exclude tides and surges it is unclear whether they are suitable for providing DSLC projections in shallow coastal regions such as the Northwestern European Shelf (NWES). One approach to addressing these shortcomings is dynamical downscaling – i.e. using a high-resolution regional model forced with output from GCMs. Here we use the regional shelf seas model AMM7 to show that, depending on the driving CMIP5 GCM, dynamical downscaling can have a large impact on DSLC simulations in the NWES region. For a business-as-usual greenhouse gas concentration scenario, we find that downscaled simulations of twenty-first century DSLC can be up to 15.5 cm smaller than DSLC in the GCM simulations along the North Sea coastline owing to unresolved processes in the GCM. Furthermore, dynamical downscaling affects the simulated time of emergence of sea-level change (SLC) above sea-level variability, and can result in differences in the projected change of the amplitude of the seasonal cycle of sea level of over 0.3 mm/yr. We find that the difference between GCM and downscaled results is of similar magnitude to the uncertainty of CMIP5 ensembles used for previous DSLC projections. Our results support a role for dynamical downscaling in future regional sea-level projections to aid coastal decision makers.

Successful Blue Economy Examples With an Emphasis on International Perspectives - Lu Wenhai; Caroline Cusack; Maria Baker; Wang Tao; Chen Mingbao; Kelli Paige; Zhang Xiaofan; Lisa Levin; Elva Escobar; Diva Amon; Yin Yue; Anja Reitz; et al. (Frontiers in Marine Science, 2019)

What are the prospects for seasonal prediction of the marine environment of the North-west European Shelf? - Jonathan Tinker; Justin Krijnen; Richard Wood; Rosa Barciela; Stephen R. Dye (Ocean Science, 2018)
Sustainable management and utilisation of the North-west European Shelf (NWS) seas could benefit from reliable forecasts of the marine environment on monthly to seasonal timescales. Recent advances in global seasonal forecast systems and regional marine reanalyses for the NWS allow us to investigate the potential for seasonal forecasts of the state of the NWS. We identify three possible approaches to address this issue: (A) basing NWS seasonal forecasts directly on output from the Met Office's GloSea5 global seasonal forecast system; (B) developing empirical downscaling relationships between large-scale climate drivers predicted by GloSea5 and the state of the NWS; and (C) dynamically downscaling GloSea5 using a regional model. We show that the GloSea5 system can be inadequate for simulating the NWS directly (approach A). We explore empirical relationships between the winter North Atlantic Oscillation (NAO) and NWS variables estimated using a regional reanalysis (approach B). We find some statistically significant relationships and present a skillful prototype seasonal forecast for English Channel sea surface temperature. We find large-scale relationships between inter-annual variability in the boundary conditions and inter-annual variability modelled on the shelf, suggesting that dynamic downscaling may be possible (approach C). We also show that for some variables there are opposing mechanisms correlated with the NAO, for which dynamic downscaling may improve on the skill possible with empirical forecasts. We conclude that there is potential for the development of reliable seasonal forecasts for the NWS and consider the research priorities for their development.

Projected sea level rise and changes in extreme storm surge and wave events during the 21st century in the region of Singapore - Heather Cannaby; Matthew D. Palmer; Tom Howard; Lucy Bricheno; Daley Calvert; Justin Krijnen; Richard Wood; Jonathan Tinker; Chris Bunney; James Harle; Andrew Saulter; Clare O'Neill; et al. (Ocean Science, 2016)
Singapore is an island state with considerable population, industries, commerce and transport located in coastal areas at elevations less than 2 m making it vulnerable to sea level rise. Mitigation against future inundation events requires a quantitative assessment of risk. To address this need, regional projections of changes in (i) long-term mean sea level and (ii) the frequency of extreme storm surge and wave events have been combined to explore potential changes to coastal flood risk over the 21st century. Local changes in time-mean sea level were evaluated using the process-based climate model data and methods presented in the United Nations Intergovernmental Panel on Climate Change Fifth Assessment Report (IPCC AR5). Regional surge and wave solutions extending from 1980 to 2100 were generated using ∼ 12 km resolution surge (Nucleus for European Modelling of the Ocean – NEMO) and wave (WaveWatchIII) models. Ocean simulations were forced by output from a selection of four downscaled ( ∼ 12 km resolution) atmospheric models, forced at the lateral boundaries by global climate model simulations generated for the IPCC AR5. Long-term trends in skew surge and significant wave height were then assessed using a generalised extreme value model, fit to the largest modelled events each year. An additional atmospheric solution downscaled from the ERA-Interim global reanalysis was used to force historical ocean model simulations extending from 1980 to 2010, enabling a quantitative assessment of model skill. Simulated historical sea-surface height and significant wave height time series were compared to tide gauge data and satellite altimetry data, respectively. Central estimates of the long-term mean sea level rise at Singapore by 2100 were projected to be 0.52 m (0.74 m) under the Representative Concentration Pathway (RCP)4.5 (8.5) scenarios. Trends in surge and significant wave height 2-year return levels were found to be statistically insignificant and/or physically very small under the more severe RCP8.5 scenario. We conclude that changes to long-term mean sea level constitute the dominant signal of change to the projected inundation risk for Singapore during the 21st century. We note that the largest recorded surge residual in the Singapore Strait of ∼ 84 cm lies between the central and upper estimates of sea level rise by 2100, highlighting the vulnerability of the region.